Penerapan Pembelajaran Praktik Wudhu Dan Solat Dalam Meningkatkan Sosial Emosional di SD Muhammadiyah Kaliabu Salaman Magelang - Putri Anggita Sari; Nasokha; Sofan Rizqi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
. In order to improve social emotions at SD Muhammadiyah Kaliabu Salaman Magelang, the objectives to be achieved in this thesis are: 1) To find out the application of ablution practice learning; 2) To ensure the implementation of learning the practice of prayer; and 3) To find out the factors that influence the implementation of learning the practice of ablution and prayer in increasing social emotions at Muhammadiyah Kaliabu Salaman Elementary School, Magelang. Qualitative descriptive research is used in this thesis. In this research, researchers collected data by means of observation, interviews and documentation (documentary study). The principal, educators and students of Muhammadiyah Kaliabu Salaman Elementary School, Magelang, were used as research subjects. Almost the same approach is used in teaching ablution and prayer at Muhammadiyah Kaliabu Salaman Elementary School: the teacher explains the material first, then gives a demonstration in front of the students, then asks the students to practice what they have learned. The practice of ablution and prayer helps shape children's social-emotional souls, makes students more able to control their emotions, increases understanding of religion, strengthens ties between teachers, and develops the social-emotional aspects of students' souls. Environmental influences, social relationships, support from those closest to the child, the role of teachers, incompatibility with peers, etc., can all have an impact on how a child shapes his social-emotional spirit.